Relationship between canalization and developmental stability of foetal rabbit limbs in two reproductive toxicological experiments. (27th March 2013) - Breno, Matteo; Bots, Jessica; Van Dongen, Stefan
Abstract : The mechanisms of developmental buffering and its relevance to the evolutionary process have recently attracted a lot of attention in both developmental and evolutionary biology. Among other things, whether the two components of developmental buffering [i.e. canalization and developmental stability (DS)] have a common basis has long been the subject of debate. In the present study, we examine the association between fluctuating asymmetry (i.e. the directionally random asymmetry of bilateral structures), a measure of DS, and between‐individual variation of long bones in over 1000 rabbit foetuses. The lack of correlations between fluctuating asymmetry and between‐individual variation at the individual, litter and treatment level, in combination with the absence of correspondence among covariance matrices, supports distinct developmental mechanisms for DS and canalization. We discuss our results in the context of recent insights into the mechanisms of developmental buffering. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 109, 434–440.